Normativity and the will : selected papers on moral psychology and practical reason - Wallace, R. Jay (Clarendon Press ; Oxford University Press, 2006)
Normativity and the Will collects fourteen important papers on moral psychology and practical reason by R. Jay Wallace, one of the leading philosophers currently working in these areas. The papers explore the interpenetration of normative and psychological issues in a series of debates that lie at the heart of moral philosophy. Part I, Reason, Desire, and the Will, discusses the nexus linking normativity to motivation, including the relations between desire and reasons, the role ofnormative considerations in explanations of action, and the normative commitments involved in willing an end (such as the requirement to adopt the necessary means). Part II, Responsibility, Identification, and Emotion, looks at questions about the rational capacities presupposed by accountableagency and the psychic factors that both inhibit and enable identification with what we do. It includes an interpretation of the Nietzschean claim that ressentiment is among the sources of modern moral consciousness. Part III, Morality and Other Normative Domains, addresses the structure of moralreasons and moral motivation, and the relations between moral demands and other normative domains (including especially the requirements of living a meaningful human life). Wallace's treatments of these topics are at once sophisticated and engaging. Taken together, they constitute an advertisement for a distinctive way of pursuing issues in moral psychology and the theory of practical reason. The book articulates and defends a unified framework for thinking about thoseissues, while offering sustained critical discussions of other influential approaches (by philosophers such as Korsgaard, McDowell, Nietzsche, Raz, Scanlon, and Williams). It should be of interest to every serious student of moral philosophy.